Glass-ceramic component, method for the production thereof and use thereof

CN123003127APending Publication Date: 2026-10-30LENS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610640608.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

由于微晶玻璃表面化学惰性较强且表面能较低,涂层难以形成牢固的化学键合,极易出现附着力差、易剥落或耐刮擦性不足的问题

Benefits of technology

[0009]本发明的有益效果至少在于:本发明的微晶玻璃构件兼顾超低雾度和超高涂层结合力,一方面能保证清晰度,确保显示色彩鲜艳真实,优化视觉体验;另一方面,增强功能性涂层附着力,防止脱落剥落,显著提升盖板的使用寿命。其独特的纳米级凹坑及其表面所具有的凸出于玻璃相表面的裸露晶相,并将表面粗糙度 Sa 控制在特定范围,在保持雾度的前提下显著提高涂层结合力,有效提升了涂层结合力同时避免雾度上升。本发明很好地满足微晶玻璃盖板在极致外观与功能集成需求下,兼具低雾度与高涂层结合力的使用要求,对破除 3C 电子产品外观件制造瓶颈、提升产品良率与用户体验具有重要现实意义。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003127A_ABST
    Figure CN123003127A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of glass-ceramics, and particularly relates to a glass-ceramic component, a preparation method and application thereof. The glass-ceramic component comprises a glass-ceramic base, the glass-ceramic base comprises a glass phase and a crystal phase, and at least one surface of the glass-ceramic base is distributed with nano-scale pits; the surface of the nano-scale pits has exposed crystal phase protruding from the surface of the glass phase; and the roughness Sa of the surface of the glass-ceramic base distributed with nano-scale pits is 8-20 nm. The glass-ceramic component of the present application can significantly improve the coating adhesion while maintaining ultra-low haze, and has important practical significance for solving the manufacturing bottleneck of current high-end 3C electronic product appearance parts, improving product yield and user experience.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass-ceramic technology, and more particularly to glass-ceramic components, their preparation methods, and applications. Background Technology

[0002] As 3C electronic products continue to evolve towards high-end, thinner, and more integrated designs, microcrystalline glass, with its excellent mechanical strength, smooth touch, and fingerprint-resistant properties, has become the preferred material for high-end cover plates and protective panels. However, in the pursuit of the ultimate aesthetic effect and functional layer bonding performance, microcrystalline glass cover plates face the technical contradiction of achieving both low haze and high coating adhesion.

[0003] On the one hand, the light transmittance of microcrystalline glass directly depends on its internal crystalline phase distribution and surface smoothness. Improper crystallization process leading to coarse grains, or insufficient surface polishing resulting in micro-scratches, will cause severe light scattering, increasing haze and damaging the mirror-like texture and visual transparency of the back cover, failing to meet the stringent optical performance standards of high-end products. On the other hand, to impart hydrophobic, oleophobic, wear-resistant, or special optical effects to the back cover, functional coatings are typically applied to its surface. Due to the strong chemical inertness and low surface energy of microcrystalline glass, coatings struggle to form strong chemical bonds, easily resulting in poor adhesion, easy peeling, or insufficient scratch resistance.

[0004] In existing technologies, surface roughening or conventional etching processes used to improve coating adhesion often drastically increase surface roughness at the microscale, thereby exacerbating light scattering and leading to a significant increase in haze. Conversely, fine polishing or densification processes performed to achieve extremely low haze may eliminate the microscopic anchoring structures required for the coating, weakening the interfacial bonding strength. Currently, the industry lacks a technical solution for microcrystalline glass components that can simultaneously optimize bulk optical uniformity and surface interfacial activity. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides microcrystalline glass components, their preparation methods, and applications. The microcrystalline glass components provided by this invention can significantly improve coating adhesion while maintaining ultra-low haze, which is of significant practical importance for overcoming current bottlenecks in the manufacturing of high-end 3C electronic product exterior components, improving product yield, and enhancing user experience.

[0006] In a first aspect, the present invention provides a microcrystalline glass component, comprising: a microcrystalline glass substrate, the microcrystalline glass substrate comprising a glass phase and a crystalline phase, wherein at least one surface of the microcrystalline glass substrate is distributed with nanoscale pits; the surface of the nanoscale pits has exposed crystalline phases protruding from the surface of the glass phase; and the roughness Sa of the surface of the microcrystalline glass substrate with nanoscale pits is 8-20 nm.

[0007] In a second aspect, the present invention provides a method for preparing the microcrystalline glass component, comprising a step of performing high-temperature chemical polishing on at least one side of the microcrystalline glass substrate material using an alkaline etchant, wherein by controlling the etching rate difference and etching depth between the crystalline phase and the glass phase, a portion of the crystalline phase is peeled off to form nanoscale pits, and an exposed crystalline phase protruding from the glass phase is formed on the surface of the nanoscale pits.

[0008] Thirdly, the present invention provides the application of the microcrystalline glass component or the microcrystalline glass component obtained by the preparation method in 3C products.

[0009] The beneficial effects of this invention are at least as follows: the microcrystalline glass component of this invention balances ultra-low haze and ultra-high coating adhesion. On the one hand, it ensures clarity, guarantees vibrant and realistic display colors, and optimizes the visual experience; on the other hand, it enhances the adhesion of functional coatings, prevents peeling and flaking, and significantly extends the service life of the cover plate. Its unique nanoscale pits and the exposed crystalline phases protruding from the glass phase surface, along with controlling the surface roughness Sa within a specific range, significantly improve coating adhesion while maintaining haze, effectively enhancing coating adhesion and preventing haze from increasing. This invention perfectly meets the requirements of microcrystalline glass cover plates for both ultimate aesthetics and functional integration, possessing both low haze and high coating adhesion. It has significant practical implications for breaking through the manufacturing bottlenecks of 3C electronic product exterior components, improving product yield, and enhancing user experience. Attached Figure Description

[0010] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0011] Figure 1 This is a SEM image of the surface of a microcrystalline glass component according to an embodiment of the present invention.

[0012] Figure 2 This is an AFM topography image and contour curve of the surface of a microcrystalline glass component according to an embodiment of the present invention.

[0013] Figure 3 This is a schematic diagram of a microcrystalline glass component according to an embodiment of the present invention. Detailed Implementation

[0014] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0015] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0016] Unless otherwise specified, the techniques or conditions described in the embodiments of this invention shall be performed in accordance with the techniques or conditions described in the literature in this field, or in accordance with the product instructions. Devices, instruments, reagents, etc., without specified manufacturers, are all conventional products that can be purchased through legitimate channels. All experimental reagents and raw materials involved are commercially available products, and all reagents are analytical grade products.

[0017] Some embodiments of the present invention provide a microcrystalline glass component, comprising: a microcrystalline glass substrate, the microcrystalline glass substrate comprising a glass phase and a crystalline phase, at least one surface of the microcrystalline glass substrate having nanoscale pits distributed thereon; the surface of the nanoscale pits having exposed crystalline phases protruding from the surface of the glass phase; the surface roughness Sa of the surface of the microcrystalline glass substrate with nanoscale pits distributed thereon is 8-20 nm. The microcrystalline glass component provided by the present invention has exposed crystalline phases protruding from the glass phase distributed on the surface of the nanoscale pits, and the exposed crystalline phases and the glass phase in the pits synergistically form a mechanical locking effect; simultaneously, the exposed crystalline phases can increase surface energy and provide active sites, strengthen interfacial chemical bonding, and significantly improve coating adhesion. Furthermore, the exposed crystalline phases have a high refractive index matching degree with the glass substrate, which can effectively reduce light scattering. The present invention controls the surface roughness Sa to 8-20 nm and utilizes the exposed crystalline phases protruding from the glass phase distributed on the surface of the nanoscale pits to achieve ultra-low haze (<3%) and ultra-high coating adhesion.

[0018] In some embodiments of the present invention, the average height of the exposed crystalline phase is 5-10 nm; for example, 5.3 nm, 5.5 nm, 5.9 nm, 6 nm, 6.5 nm, 6.8 nm, 7 nm, 7.5 nm, 8 nm, 8.5 nm, etc. In these embodiments, the average height of the exposed crystalline phase refers to the average height of the exposed crystalline phase protruding from the glass phase on the surface of the nanoscale pits. The average height of the exposed crystalline phase in this invention allows for better embedding of the exposed crystalline phase into the microcrystalline glass matrix, resulting in structural stability and resistance to detachment.

[0019] In some embodiments of the present invention, the height range of the exposed crystalline phase is 2-20 nm; for example, 3 nm, 4 nm, 5 nm, 5.5 nm, 6 nm, 7 nm, 8 nm, 8.5 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 18 nm, 19 nm, etc.

[0020] In some embodiments of the present invention, the density of the exposed crystalline phase is 12-23 particles / μm. 2 For example, 12 cells / μm 2 13 / μm 2 14 per μm 2 15 cells / μm 2 16 per μm 2 18 per μm 2 19 / μm 2 20 cells / μm 2 22 per μm 2 The optimal height and density of the exposed crystalline phase can achieve better haze and coating adhesion.

[0021] In this embodiment of the invention, by optimizing and controlling the exposed crystalline phase, the protruding crystalline phase is appropriately embedded inside the microcrystalline glass matrix, resulting in a tight structural bond and excellent overall stability. This effectively prevents the crystalline phase particles from loosening, falling off, or peeling off and failing. Combined with the dual interface effect of mechanical locking and chemical bonding formed by the synergistic interaction between the nano-pits and the crystalline phase protrusions, the coating adhesion is significantly improved, while light scattering is suppressed and haze is optimized, achieving a comprehensive performance of high coating adhesion, structural stability, and excellent optical properties in the component.

[0022] In a preferred embodiment of the present invention, the average height of the exposed crystalline phase is 5-8 nm, preferably 6-8 nm; the height range of the exposed crystalline phase is 2-19 nm, preferably 2-18 nm; and the density of the exposed crystalline phase is 13-16 particles / μm. 2 Preferably 13-15 per μm 2 .

[0023] In some embodiments of the present invention, the surface roughness Sa of the microcrystalline glass substrate with nanoscale pits is 10-15 nm; for example, 10 nm, 10.3 nm, 10.5 nm, 11 nm, 12 nm, 13 nm, 14 nm, 14.6 nm, 14.7 nm, 14.8 nm, etc.

[0024] In some embodiments of the present invention, the average depth of the nanoscale pits is 75-160 nm; for example, 78 nm, 79 nm, 80 nm, 81 nm, 82 nm, 83 nm, 84 nm, 88 nm, 89 nm, 90 nm, 93 nm, 95 nm, 98 nm, 100 nm, 115 nm, 120 nm, 125 nm, 130 nm, 140 nm, 150 nm, 155 nm, etc. By controlling the average depth of the nanoscale pits to 75-160 nm, and by optimizing the surface roughness Sa of the microcrystalline glass substrate and the average depth of the nanoscale pits, the present invention can balance optical scattering and interfacial bonding effects, effectively improve the low-haze appearance and high coating adhesion, and achieve optimal matching of various performance characteristics.

[0025] In a preferred embodiment of the present invention, the surface roughness Sa of the microcrystalline glass substrate with distributed nanoscale pits is 10-14.8 nm, preferably 10.3-14.6 nm; the average depth of the nanoscale pits is 75-125 nm, preferably 75-120 nm. The surface roughness Sa and average depth of the nanoscale pits on the microcrystalline glass substrate of the present invention achieve better haze and coating adhesion.

[0026] In some embodiments of the present invention, the haze of the microcrystalline glass component is less than 3%; for example, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.4%, 1.5%, 1.6%, 2%, 2.5%, 2.8%, etc.

[0027] In this embodiment of the invention, the nanoscale pits and the exposed crystalline phase are obtained by high-temperature chemical polishing of at least one side of the microcrystalline glass substrate material, based on the difference in etching rates between the crystalline phase and the glass phase, and by controlling the etching depth.

[0028] In some embodiments of the present invention, the haze of the microcrystalline glass substrate is less than 0.3%; for example, 0.28%, 0.26%, 0.25%, 0.21%, 0.2%, 0.15%, 0.12%, 0.1%, etc.

[0029] In some embodiments of the present invention, the microcrystalline glass substrate is lithium aluminum silicon, magnesium aluminum silicon, zinc aluminum silicon or borosilicate microcrystalline glass, preferably lithium aluminum silicon microcrystalline glass, wherein the crystal phase of the lithium aluminum silicon microcrystalline glass is lithium feldspar and lithium disilicate.

[0030] In some embodiments of the present invention, the size of the crystalline phase particles in the microcrystalline glass matrix is ​​20-50 nm.

[0031] In some embodiments of the present invention, the content of the crystalline phase in the microcrystalline glass matrix is ​​70-80 wt.%.

[0032] In some embodiments of this invention, the haze of the microcrystalline glass matrix is ​​less than 0.3%. This invention utilizes the microcrystalline glass matrix with controlled crystalline phase particle size and content, and selects matrix raw materials with low haze. This facilitates enhanced interfacial bonding while effectively maintaining excellent light transmission and low haze optical quality. The haze of lithium aluminum silicon microcrystalline glass is typically controlled between 0.1% and 0.3%. Lithium feldspar, as the main crystalline phase, imparts excellent thermal stability and chemical durability to the material; lithium disilicate, through nanoscale precipitation, significantly enhances mechanical strength and fracture toughness. The synergistic regulation of grain size and refractive index matching between the two not only suppresses light scattering to maintain high transparency but also effectively disperses stress through the microcrystalline network, achieving a balance between high strength and low haze.

[0033] In some preferred embodiments of the present invention, the microcrystalline glass matrix contains 70-75 wt.% SiO2, 10-15 wt.% Li2O, 5-10 wt.% Al2O3, 5-10 wt.% ZrO2, 2-4 wt.% P2O5, 1-3 wt.% Na2O, and 0.5-1 wt.% CaO.

[0034] In some specific embodiments of the present invention, the bonding force between the microcrystalline glass component and the coating is 5 B.

[0035] In a preferred embodiment of the present invention, the surface roughness Sa of the microcrystalline glass substrate with nanoscale pits is 0.0014%-0.0037% of the thickness of the microcrystalline glass component.

[0036] In a preferred embodiment of the present invention, the average depth of the nanoscale pits is 0.013%-0.03% of the thickness of the glass-ceramic component. In this embodiment, the haze and coating adhesion of the glass-ceramic component are closely related to the surface roughness of the substrate of the nanoscale pits, the average depth of the nanoscale pits, and the exposed crystalline phase. To ensure the overall performance of the component, the roughness Sa is preferably controlled within the range of 0.0014-0.0037% of the component thickness, which ensures both the adhesion of the glass-ceramic component and controls the haze to be less than 0.3%. Controlling the average depth of the nanoscale pits to 0.013-0.03% of the component thickness balances optical scattering and interfacial bonding effects, effectively improving the low-haze appearance and high coating adhesion, achieving an excellent match of various performance characteristics. The height range of the exposed crystalline phase further effectively ensures that the crystalline phase is embedded in the glass-ceramic, resulting in structural stability and preventing detachment.

[0037] Some embodiments of the present invention also provide a method for preparing the microcrystalline glass component, including a step of performing high-temperature chemical polishing on at least one side of the microcrystalline glass substrate material using an alkaline etchant, and by controlling the etching rate difference and etching depth between the crystalline phase and the glass phase, partially crystalline phase is peeled off to form nanoscale pits, and exposed crystalline phase protruding from the glass phase is formed on the surface of the nanoscale pits.

[0038] In a preferred embodiment, the high-temperature chemical polishing treatment is performed at a temperature of 150-350 °C for 1-300 min; the alkaline etchant contains OH... - Solution or molten salt.

[0039] In a preferred embodiment of the present invention, a heat treatment step is further included before the high-temperature polishing treatment. The present invention increases the crystalline phase content in the glass-ceramic matrix through heat treatment; alternatively, a glass-ceramic matrix material that meets the crystalline phase requirements can be directly used, and the present invention does not limit this approach.

[0040] In a preferred embodiment of the present invention, the heat treatment temperature is 720-800 ℃ and the time is 240-900 s.

[0041] In a preferred embodiment of the present invention, a polishing process is further included, wherein the polishing process includes double-sided polishing of the microcrystalline glass before the high-temperature chemical polishing treatment and single-sided polishing of the microcrystalline glass after the high-temperature chemical polishing treatment.

[0042] In a preferred embodiment of the present invention, the microcrystalline glass substrate is subjected to hot bending forming, and then cooled to obtain hot-bent microcrystalline glass.

[0043] In some specific embodiments of the present invention, the method for preparing the microcrystalline glass component includes: 1) Hot Bending: The glass-ceramic is placed in a hot bending mold and heated to a set temperature of 720-800 ℃ at a heating rate of 30-150 ℃ / min, and held at that temperature for 240-900 s. A uniform pressure of 0.4-1.6 MPa is applied throughout the high-temperature holding period, followed by slow cooling to room temperature to reduce internal stress and ensure strength. Hot bending allows the glass-ceramic matrix to form a specific shape. Heat treatment can slightly increase the crystalline phase content of the glass-ceramic, which is beneficial for the subsequent formation of nanoscale pits and exposed crystalline phases.

[0044] 2) Double-sided polishing: Remove the excessive crystallization layer, defects, pits and rough textures on the surface of hot-bent glass, and control the roughness Sa≤1nm and haze≤0.3%.

[0045] 3) High-temperature chemical polishing: The polished glass is placed in an alkaline etchant (containing OH) with an alkali compound mass ratio of 40-80 wt.%. -In a solution or molten salt, the chemical polishing temperature is set to 150-350 ℃ and the chemical polishing time is 1-300 min. During the chemical polishing process, continuous bubbling is carried out to promote the flow of the chemical polishing solution and ensure that the crystalline phase particles are removed in time, thereby achieving uniform etching. The bubbling pressure is 2-4 bar. By changing the chemical polishing process parameters, the etching rate difference between the crystalline phase and the glass phase is controlled, thereby ensuring a low pit roughness and exposing the surface crystalline phase to form an exposed crystalline phase that is not easy to fall off.

[0046] 4) Single-sided polishing: The side of the chemically polished glass with nanoscale pits and exposed crystal phases is retained, while the defects, pits and rough textures on the other side of the chemically polished glass are removed, and the roughness Sa≤1nm is controlled.

[0047] Some embodiments of the present invention also provide the application of the microcrystalline glass component or the microcrystalline glass component obtained by the preparation method in 3C products. The 3C products referred to in this invention are a collective term for computer products, communication products, and consumer electronics products. Preferably, the present invention applies the microcrystalline glass component to the front and back covers of the 3C products.

[0048] Performance advantages of some embodiments of the present invention: Balancing ultra-low haze and high coating adhesion, it improves clarity, ensures vibrant and realistic colors, and optimizes the visual experience; on the other hand, it enhances the adhesion of functional coatings, prevents peeling and flaking, and significantly extends the service life of the cover plate. Structural advantages: The combination of specific nanoscale pits and exposed crystalline phases significantly improves coating adhesion while maintaining haze.

[0049] In this embodiment of the invention, the term haze refers to the proportion of luminous flux that deviates from the original direction of propagation (usually more than 2.5° from the angle of incidence) when light passes through a material. The higher the haze, the more "blurry" or "whitish" the material appears, and the lower the clarity when viewing objects through it; conversely, the lower the haze, the more "clear and transparent" the material appears.

[0050] In this embodiment of the invention, the haze testing method is as follows: A Shimadzu UV-3700 ultraviolet spectrophotometer equipped with an integrating sphere accessory is used, with a wavelength range of 380-780 nm and a medium scanning speed. Total transmittance and scattered transmittance are measured separately, and the haze value is calculated according to the formula (haze = scattered transmittance / total transmittance). 100%.

[0051] In this embodiment of the invention, the term coating adhesion refers to the degree of firmness of the bond between the functional coating and the substrate. It is one of the most critical indicators for measuring the quality of functional components, directly determining the component's durability, appearance quality, and service life.

[0052] In this embodiment of the invention, the coating adhesion test method is as follows: First, an organosilicon photoresist coating (approximately 1 μm thick) and an epoxy resin ink coating (approximately 50 μm thick) are sequentially coated on the surface of the component. Then, the component is placed in hot water at 80 °C for 30 min. After that, a cross-cut tester is used to cut a 1 mm × 1 mm grid, totaling 100 squares, on the coating surface. Subsequently, 3M tape is used to firmly adhere the grid and then quickly peel it off. The coating peeling at the grid is observed. According to the ASTM D3359 standard rating, 5B is no peeling (i.e., the coating peeling area is 0%), 4B is peeling 0-5%, 3B is peeling 5-15%, 2B is peeling 15-35%, 1B is peeling 35-65%, and 0B is peeling more than 65%.

[0053] In this embodiment of the invention, the microcrystalline glass substrate is lithium aluminum silicon microcrystalline glass, which is composed of a crystalline phase (lithium feldspar and lithium disilicate) and a glassy phase. The crystalline phase particle size is 30 nm, the crystalline phase content is 75 wt.%, and the haze is 0.22%. In this embodiment of the invention, the alkaline etchant used can be selected from NaOH solution, KOH solution, or a mixed molten salt of KOH and KNO3.

[0054] Example 1 The method for preparing the microcrystalline glass component provided in this embodiment includes: 1) Hot bending: The microcrystalline glass substrate is placed in a hot bending mold and heated to the set temperature of 760 ℃ at a heating rate of 90 ℃ / min, and held at that temperature for 600s. At the same time, a uniform pressure of 0.8 MPa is applied throughout the high-temperature holding stage, and then it is slowly cooled to room temperature.

[0055] 2) Double-sided polishing: Remove the excessive crystallization layer, defects, pits and rough textures on the surface of hot-bent glass, and control the roughness Sa≤1nm and haze≤0.3%.

[0056] 3) High-temperature chemical polishing: Place the polished glass in an alkaline etchant (containing KOH and KNO3) with an alkali compound mass ratio of 50wt.%, set the chemical polishing temperature to 250℃, and the chemical polishing time to 90min. During the chemical polishing process, continuous bubbling is carried out at a bubbling pressure of 3bar.

[0057] 4) Single-sided polishing: The side of the chemically polished glass with exposed crystalline phase is retained, while defects, pits, and rough textures on the other side of the chemically polished glass are removed, and the roughness Sa≤1nm is controlled.

[0058] The microcrystalline glass component provided in this embodiment includes a microcrystalline glass substrate, which includes a glass phase and a crystalline phase. One surface of the microcrystalline glass substrate is distributed with nanoscale pits. The surface of the nanoscale pits has exposed crystalline phases protruding from the surface of the glass phase. See Table 1 for details.

[0059] Example 2 The method for preparing the microcrystalline glass component provided in this embodiment includes: 1) Hot bending: The microcrystalline glass substrate is placed in a hot bending mold and heated to the set temperature of 760 ℃ at a heating rate of 90 ℃ / min, and held at that temperature for 600s. At the same time, a uniform pressure of 0.8 MPa is applied throughout the high-temperature holding stage, and then it is slowly cooled to room temperature.

[0060] 2) Double-sided polishing: Remove the excessive crystallization layer, defects, pits and rough textures on the surface of hot-bent glass, and control the roughness Sa≤1nm and haze≤0.3%.

[0061] 3) High-temperature chemical polishing: Place the polished glass in an alkaline etchant (containing KOH and H2O) with an alkali compound mass ratio of 70wt.%, set the chemical polishing temperature to 170℃, and the chemical polishing time to 330min. During the chemical polishing process, continuous bubbling is carried out at a bubbling pressure of 3bar.

[0062] 4) Single-sided polishing: The side of the chemically polished glass with exposed crystalline phase is retained, while defects, pits, and rough textures on the other side of the chemically polished glass are removed, and the roughness Sa≤1nm is controlled.

[0063] The microcrystalline glass component provided in this embodiment is the same as that in Embodiment 1, with the differences shown in Table 1.

[0064] Example 3 The method for preparing the microcrystalline glass component provided in this embodiment includes: 1) Hot bending: The microcrystalline glass substrate is placed in a hot bending mold and heated to the set temperature of 760 ℃ at a heating rate of 90 ℃ / min, and held at that temperature for 600s. At the same time, a uniform pressure of 0.8 MPa is applied throughout the high-temperature holding stage, and then it is slowly cooled to room temperature.

[0065] 2) Double-sided polishing: Remove the excessive crystallization layer, defects, pits and rough textures on the surface of hot-bent glass, and control the roughness Sa≤1nm and haze≤0.3%.

[0066] 3) High-temperature chemical polishing: Place the polished glass in an alkaline etchant (containing NaOH and H2O) with an alkali compound mass ratio of 70wt.%, set the chemical polishing temperature to 170℃, and the chemical polishing time to 45min. During the chemical polishing process, continuous bubbling is carried out at a bubbling pressure of 3bar.

[0067] 4) Single-sided polishing preserves the exposed crystalline phase on one side of the chemically polished glass, while removing defects, pits, and rough textures on the other side of the chemically polished glass, controlling the roughness Sa≤1nm.

[0068] The microcrystalline glass component provided in this embodiment is the same as that in Embodiment 1, with the differences shown in Table 1.

[0069] Example 4 The method for preparing the microcrystalline glass component provided in this embodiment includes: 1) Hot bending: The microcrystalline glass substrate is placed in a hot bending mold and heated to the set temperature of 760 ℃ at a heating rate of 90 ℃ / min, and held at that temperature for 600s. At the same time, a uniform pressure of 0.8 MPa is applied throughout the high-temperature holding stage, and then it is slowly cooled to room temperature.

[0070] 2) Double-sided polishing: Remove the excessive crystallization layer, defects, pits and rough textures on the surface of hot-bent glass, and control the roughness Sa≤1nm and haze≤0.3%.

[0071] 3) High-temperature chemical polishing: Place the polished glass in an alkaline etchant (containing KOH and KNO3) with an alkali compound mass ratio of 50wt.%, set the chemical polishing temperature to 260℃, and the chemical polishing time to 60min. During the chemical polishing process, continuous bubbling is carried out at a bubbling pressure of 3bar.

[0072] 4) Single-sided polishing preserves the exposed crystalline phase on one side of the chemically polished glass, while removing defects, pits, and rough textures on the other side of the chemically polished glass, controlling the roughness Sa≤1nm.

[0073] The microcrystalline glass component provided in this embodiment is the same as that in Embodiment 1, with the differences shown in Table 1.

[0074] Example 5 The method for preparing the microcrystalline glass component provided in this embodiment includes: 1) Hot bending: The microcrystalline glass substrate is placed in a hot bending mold and heated to the set temperature of 760 ℃ at a heating rate of 90 ℃ / min, and held at that temperature for 600s. At the same time, a uniform pressure of 0.8 MPa is applied throughout the high-temperature holding stage, and then it is slowly cooled to room temperature.

[0075] 2) Double-sided polishing: Remove the excessive crystallization layer, defects, pits and rough textures on the surface of hot-bent glass, and control the roughness Sa≤1nm and haze≤0.3%.

[0076] 3) High-temperature chemical polishing: Place the polished glass in an alkaline etchant (containing KOH and H2O) with an alkali compound mass ratio of 80wt.%, set the chemical polishing temperature to 200℃, and the chemical polishing time to 210min. During the chemical polishing process, continuous bubbling is carried out at a bubbling pressure of 3bar.

[0077] 4) Single-sided polishing preserves the exposed crystalline phase on one side of the chemically polished glass, while removing defects, pits, and rough textures on the other side of the chemically polished glass, controlling the roughness Sa≤1nm.

[0078] The microcrystalline glass component provided in this embodiment is the same as that in Embodiment 1, with the differences shown in Table 1.

[0079] Example 6 The method for preparing the microcrystalline glass component provided in this embodiment includes: 1) Hot bending: The microcrystalline glass substrate is placed in a hot bending mold and heated to the set temperature of 760 ℃ at a heating rate of 90 ℃ / min, and held at that temperature for 600s. At the same time, a uniform pressure of 0.8 MPa is applied throughout the high-temperature holding stage, and then it is slowly cooled to room temperature.

[0080] 2) Double-sided polishing: Remove the excessive crystallization layer, defects, pits and rough textures on the surface of hot-bent glass, and control the roughness Sa≤1nm and haze≤0.3%.

[0081] 3) High-temperature chemical polishing: Place the polished glass in an alkaline etchant (containing KOH and H2O) with an alkali compound mass ratio of 70wt.%, set the chemical polishing temperature to 175℃, and the chemical polishing time to 300min. During the chemical polishing process, continuous bubbling is carried out at a bubbling pressure of 3bar.

[0082] 4) Single-sided polishing preserves the exposed crystalline phase on one side of the chemically polished glass, while removing defects, pits, and rough textures on the other side of the chemically polished glass, controlling the roughness Sa≤1nm.

[0083] The microcrystalline glass component provided in this embodiment is the same as that in Embodiment 1, with the differences shown in Table 1.

[0084] Comparative Examples 1-4 The nanoscale pits, exposed crystalline phases, or specific parameters of the microcrystalline glass components provided in Comparative Examples 1-4 are different from those in Example 1, as detailed in Table 1.

[0085] Figure 1 This is a SEM image of the surface of the microcrystalline glass component in Example 1. Figure 1 It can be seen that the surface of the component has high flatness, no obvious cracks or peeling, and exposed nanoscale microcrystalline structure, while retaining the intrinsic structural characteristics of microcrystalline glass. It is evident that it is suitable for application scenarios that are sensitive to surface quality and microstructure. Figure 2 The AFM morphology and profile curves of the microcrystalline glass component surface in Example 1 are shown below. Figure 2 The AFM morphology images show that the surface of the component consists of many nanoscale pits of varying sizes, with a large number of crystalline phase particles clearly present within these pits. These nanoscale pits maintain the roughness Sa within a specific range. Figure 2As can be seen from the contour curve, there are finer exposed crystalline phases on the surface of the pits. Combined with the AFM image, it can be seen that the surface consists of a glass matrix and exposed crystalline phases. The crystalline phases are protruding and exposed, while the glass phase is recessed, with the glass phase holding the crystalline phases on the glass matrix. Therefore, the microcrystalline glass component of this embodiment includes a microcrystalline glass matrix, which comprises a glass phase and a crystalline phase; at least one surface of the microcrystalline glass matrix has nanoscale pits distributed on it; wherein, the surface of the nanoscale pits consists of a glass phase and exposed crystalline phases protruding from the surface of the glass phase, and the microcrystalline glass of the nanoscale pits has the same composition as the matrix. A schematic diagram of this microcrystalline glass component is shown below. Figure 3 The pits and exposed crystalline phases are caused by the difference in etching rates between the crystalline and glassy phases. The advantages of exposed crystalline phases are twofold: firstly, the glassy phase in the pits creates a mechanical locking effect, while the convex crystalline phase provides high surface energy and active sites, enhancing chemical bonding and significantly improving coating adhesion; secondly, the refractive index of the convex crystalline phase is similar to that of the glass matrix, resulting in weak light scattering. Furthermore, the height range of the exposed crystalline phase is much smaller than the wavelength of visible light, causing light waves to primarily diffract rather than scatter, maintaining the directionality of transmitted light and having almost no impact on component haze. In other words, exposed crystalline phases result in lower haze for components with the same coating adhesion. Increased pit depth, tilt, and width (manifested as roughness) all lead to a larger surface area of ​​the component, more scattering centers, and stronger scattered light intensity, thus increasing haze. The pits on the component surface and the exposed crystalline phase on the pit surface significantly increase the contact area with the coating, ultimately greatly improving the coating adhesion of the component.

[0086] Table 1 Test results of Examples 1-6 and Comparative Examples 1-4

[0087] Table 1 illustrates that by controlling the surface roughness of the substrate with nanoscale pits, the average depth of the nanoscale pits, and the average height and density of the exposed crystalline phase within appropriate ranges, microcrystalline glass components with ultra-low haze and high coating adhesion can be obtained. Examples 1 and 4 show that, under conditions of similar roughness and average depth of nanoscale pits, the exposed crystalline phase can significantly increase the coating adhesion of the component. Examples 1-6 demonstrate that by optimizing the average depth of the nanoscale pits, the roughness Sa, and the exposed crystalline phase parameters, components can possess both excellent coating adhesion and lower haze.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A microcrystalline glass component, characterized in that, The invention includes a microcrystalline glass substrate, the microcrystalline glass substrate comprising a glass phase and a crystalline phase, and at least one surface of the microcrystalline glass substrate having nanoscale pits distributed thereon. The surface of the nanoscale pits has exposed crystalline phases that protrude from the glass phase surface; The surface roughness Sa of the microcrystalline glass substrate with nanoscale pits is 8-20 nm.

2. The microcrystalline glass component according to claim 1, characterized in that, The average height of the exposed crystalline phase is 5-10 nm; And / or, the height of the exposed crystalline phase ranges from 2 to 20 nm; And / or, the density of the exposed crystalline phase is 12-23 particles / μm. 2 .

3. The microcrystalline glass component according to claim 1, characterized in that, The surface roughness Sa of the microcrystalline glass substrate with nanoscale pits is 10-15 nm. And / or, the average depth of the nanoscale pits is 75-160 nm.

4. The microcrystalline glass component according to any one of claims 1-3, characterized in that, The haze of the microcrystalline glass component is less than 3.

5. The microcrystalline glass component according to any one of claims 1-3, characterized in that, The microcrystalline glass substrate is lithium aluminum silicon, magnesium aluminum silicon, zinc aluminum silicon, or borosilicate microcrystalline glass, preferably lithium aluminum silicon microcrystalline glass, and the crystal phase of the lithium aluminum silicon microcrystalline glass is lithium feldspar and lithium disilicate.

6. The microcrystalline glass component according to claim 5, characterized in that, The crystal phase particles in the microcrystalline glass matrix have a size of 20-50 nm. And / or, the content of the crystalline phase in the microcrystalline glass matrix is ​​70-80 wt.%; And / or, the haze of the microcrystalline glass matrix material is less than 0.3%.

7. The microcrystalline glass component according to any one of claims 1-3, characterized in that, The surface roughness Sa of the microcrystalline glass substrate with nanoscale pits is 0.0014%-0.0037% of the thickness of the microcrystalline glass component; And / or, the average depth of the nanoscale pits is 0.013%-0.03% of the thickness of the microcrystalline glass component.

8. A method for preparing the microcrystalline glass component according to any one of claims 1-7, characterized in that, The process includes a step of high-temperature chemical polishing of at least one side of the microcrystalline glass substrate material using an alkaline etchant. By controlling the difference in etching rate and etching depth between the crystalline phase and the glass phase, a portion of the crystalline phase is peeled off to form nanoscale pits, and an exposed crystalline phase protruding from the glass phase is formed on the surface of the nanoscale pits.

9. The method for preparing a microcrystalline glass component according to claim 8, characterized in that, The high-temperature chemical polishing process includes: subjecting the microcrystalline glass substrate to high-temperature chemical polishing using an alkaline etchant, with continuous bubbling during the process. Or, a heat treatment step may be included before the high-temperature chemical polishing treatment; Or, it also includes a polishing process, wherein the polishing process includes double-sided polishing of the microcrystalline glass before the high-temperature chemical polishing treatment and single-sided polishing of the microcrystalline glass after the high-temperature chemical polishing treatment; Alternatively, the microcrystalline glass substrate is hot-bent and then cooled to obtain hot-bent microcrystalline glass.

10. The application of the microcrystalline glass component according to any one of claims 1-7 or the microcrystalline glass component obtained by the preparation method according to claim 8 or 9 in 3C products; preferably, the microcrystalline glass component is applied to the front and back covers of the 3C product.